If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x(4x + -3) = 0 Reorder the terms: 5x(-3 + 4x) = 0 (-3 * 5x + 4x * 5x) = 0 (-15x + 20x2) = 0 Solving -15x + 20x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '5x'. 5x(-3 + 4x) = 0 Ignore the factor 5.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-3 + 4x)' equal to zero and attempt to solve: Simplifying -3 + 4x = 0 Solving -3 + 4x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + 4x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 4x = 0 + 3 4x = 0 + 3 Combine like terms: 0 + 3 = 3 4x = 3 Divide each side by '4'. x = 0.75 Simplifying x = 0.75Solution
x = {0, 0.75}
| 9x-10y=-7 | | 10(x-1)/2x+10x=5 | | (3p^2-q^2)-(4p^2-7q^2)= | | 8(x+3)+7=71 | | (4x^2+5x+1)-(3x^2-7x+4)= | | 29.25/0.36 | | (-3m^2+8n^2-6n)-[(8m^2-6m+2n)+(-8m^2)+4n^2]= | | 144+81= | | 5xn=4.5 | | 10(x-1)/2x+10 | | x=12+9 | | 45/18=9/x | | -4/5*(4*-34/4-1) | | (2)/(2x-5)=-2 | | -1/4x^2-x-8=0 | | -34/4 | | 2x+5x=-15x-6x | | x/6=12/8 | | 20/16=70/x | | 6/12=n/42 | | -4/5*(4a-1)=28 | | F(x)=-3x-8f(2) | | 5+4/x | | 3/x+2/5 | | 5/x-2/x | | 3/5(30x) | | 12(4x-8)=4(12x+9) | | 6+8n-4=9n+32-7n | | 2/5n+4=20 | | X/32-18=-3 | | 7m+8m=120 | | 5v^2+3v=0 |